Pengaruh kredibilitas merek terhadap word of mouth melalui customer satisfaction dan service quality - Sherly, Sherly; Fransisca, Yuniati; Sembiring, Ulung; Ahmaddien, Iskandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of the retail business has become very competitive due to offline and online competition. Business owners must provide the best service to customers because the dynamic behavior of customers allows them to try other brands if their needs are not met. Because the number of competitors continues to increase, companies must have good positioning and credibility to retain their customers and provide positive word of mouth. The purpose of this line research is to find out the effect of brand credibility on word of mouth through customer satisfaction and service quality as intervening variables at Carrefour Retail. The sampling technique used in this research is non-probability purposive sampling. While the analysis technique uses Partial Least Square (PLS)-Structural Equation Modeling (SEM). Respondents were taken from 230 Carrefour customers in Yogyakarta with certain characteristics. The results show that customer satisfaction and service quality are intervening variables between brand credibility and word of mouth; there is an effect of brand credibility on customer satisfaction and service quality; there is an effect of customer satisfaction and service quality on word of mouth; and there is an effect of customer satisfaction and quality on customer satisfaction. Service to Word of Mouth The influence of customer satisfaction on service quality.